1993
DOI: 10.1007/bf01623826
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone formation in patients with osteoporosis associated with inflammatory bowel disease

Abstract: The pathophysiology of bone loss associated with inflammatory bowel disease has not been clearly defined. In this study we have performed a detailed histomorphometric analysis of iliac crest bone obtained from 19 patients with inflammatory bowel disease in whom a diagnosis of osteoporosis had been made. Eleven subjects were receiving prednisolone at the time of their biopsy. Comparison with control values demonstrated a highly significant reduction in trabecular bone area in the patient group (p < 0.001). Wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…2 In Crohn's disease, the situation may be complicated by the administration of oral glucocorticoids, but is not entirely steroidrelated. 3,4 The osteoporosis seen in female patients with Crohn's disease can be prevented by sex hormone replacement therapy (HRT). 5,6 Jejunoileal bypass surgery has been performed for morbid obesity and, more recently, for hyperlipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…2 In Crohn's disease, the situation may be complicated by the administration of oral glucocorticoids, but is not entirely steroidrelated. 3,4 The osteoporosis seen in female patients with Crohn's disease can be prevented by sex hormone replacement therapy (HRT). 5,6 Jejunoileal bypass surgery has been performed for morbid obesity and, more recently, for hyperlipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports in adults with IBD suggest that bone loss results is due to increased bone resorption, 8 -11 while others have reported decreased bone formation relative to bone resorption. 12 In developing children it is likely that IBD primarily affects bone formation and modeling, but this has not been studied.…”
mentioning
confidence: 99%
“…Histomorphometric studies on adult IBD patients have shown that both osteomalacia and osteoporosis can occur following small bowel resection [11,12]. In adults who suffered from osteoporosis in the context of long-standing IBD, a markedly low trabecular bone volume and a negative remodeling balance on trabecular bone surfaces were found [13]. However, to our knowledge, histomorphometric data are not available for pediatric IBD or for newly diagnosed IBD in either children or adults.…”
Section: Introductionmentioning
confidence: 64%
“…This is somewhat surprising, as histomorphometric studies in adults who suffered from osteoporosis in the context of IBD have revealed markedly low trabecular bone volume [13]. Similarly, animal models of IBD are characterized by a decrease in the amount of trabecular bone after induction of IBD, at least in mature animals [32,33].…”
Section: Discussionmentioning
confidence: 87%